2019
DOI: 10.1007/s11121-019-01076-4
|View full text |Cite
|
Sign up to set email alerts
|

The Correspondence Between Causal and Traditional Mediation Analysis: the Link Is the Mediator by Treatment Interaction

Abstract: Mediation analysis is a methodology used to understand how and why behavioral phenomena occur. New mediation methods based on the potential outcomes framework are a seminal advancement for mediation analysis because they focus on the causal basis of mediation. Despite the importance of the potential outcomes framework in other fields, the methods are not well known in prevention and other disciplines. The interaction of a treatment (X) and a mediator (M) on an outcome variable (Y) is central to the potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 34 publications
0
109
0
Order By: Relevance
“…It seems rare to observe a statistically significant XM interaction in practice (Anthopolos et al, 2014;Bauer & Scheim, 2019). An explanation might be that researchers choose mediators that are unlikely to have differential effects across the exposure groups (MacKinnon et al, 2020). Furthermore, significance tests of the h coefficient and the mediated interaction, i.e., ha, are underpowered in small samples and for small effect sizes (MacKinnon et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems rare to observe a statistically significant XM interaction in practice (Anthopolos et al, 2014;Bauer & Scheim, 2019). An explanation might be that researchers choose mediators that are unlikely to have differential effects across the exposure groups (MacKinnon et al, 2020). Furthermore, significance tests of the h coefficient and the mediated interaction, i.e., ha, are underpowered in small samples and for small effect sizes (MacKinnon et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To assess whether the methodology described by MacKinnon et al (2020) is also successful for the estimation of causal effects for mediation models with a continuous mediator and binary outcome, we analytically compared the causal estimators for models with a continuous mediator and a continuous outcome with the causal estimators for models with a continuous mediator and a binary outcome. Table 2 shows the results of these analytical comparisons.…”
Section: Analytical Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, rarely have mechanisms of how policies affect outcomes been studied, especially through formal mediation analyses. The field of prevention science has articulated theoretical and methodological standards for the study of causal mechanisms through mediation analyses (Gottfredson et al 2015 ; MacKinnon et al 2020 ); Wiedermann et al 2019 ). Theory, measurement of hypothesized mediators, and mediation analysis would contribute to the existing scientific basis of laws’ effects on MEB development, health, and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…When the X and M interaction is non-zero, Pearl (2001) demonstrated that the sum of the natural direct and indirect effects equal to the total effect (TE) (i.e., TE − NDE = NIE) at selected levels of X and, importantly, this result also holds in models with non-linear effects such as logistic regression. MacKinnon et al (2020) illustrates the correspondence between potential outcomes and traditional estimators of the indirect effect when the X and M interaction is non-zero, in the form of simple direct and indirect effects.…”
Section: Introductionmentioning
confidence: 99%